Serum selenium in critically ill patients: Profile and supplementation in a depleted region. Issue 6 (3rd April 2020) - Broman, Lars Mikael; Bernardson, Anna; Bursell, Karin; Wernerman, Jan; Fläring, Urban; Tjäder, Inga
Abstract : Background: General selenium supplementation to intensive care unit (ICU) patients in regions with selenium‐rich soil does not improve outcomes. Still selenium supplementation may reduce morbidity and mortality in patients with low‐serum selenium concentration (S‐Se) in selenium‐poor areas who respond to treatment. The primary aim of this observational study was to investigate S‐Se in a selenium‐deficient region at time of intensive care admission, and in addition to monitor S‐Se during high‐dose selenium supplementation for safety. Methods: We measured S‐Se in 100 consecutive patients admitted to a tertiary general ICU. After initial sampling, high‐dose intravenous (iv) selenium supplementation was administered up to 20 days. Results: At admission, in 95% of the cases, S‐Se was below the saturation level for selenoenzymes, in 91%, below the Swedish reference level, and in 71%, below the level where selenoenzyme function may be impaired. At day 5 of substitution, all patients still remaining in the ICU (n = 26) were within the range for enzyme function, 12% were below reference, and 24% did not reach full enzymatic saturation. At day 10 and forward, all patients were within target for treatment. No patients were at risk for toxic S‐Se concentration. Conclusions: S‐Se concentration was substantially lower compared to normal values at ICU admission in this cohort of unselected Swedish critical care patients. Selenium supplementation restituted S‐Se to levels corresponding to enzymatic saturation and the Swedish reference interval for all subjects remaining in the ICU on day 5.